2015
DOI: 10.1177/1941738115607445
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Functional Movement Screen as an Injury Prediction Tool Among Active Adult Populations

Abstract: Context:The Functional Movement Screen (FMS) is an assessment tool for quality of human movement. Research reports a significant difference between FMS scores of subjects who later experienced injury and those who remain uninjured.Objective:To systematically review literature related to predictive validity of the FMS. From the aggregated data, a meta-analysis was conducted to determine the prognostic accuracy of the FMS.Data Sources:PubMed, Ebscohost, Google Scholar, and the Cochrane Review databases were sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
101
2
7

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 116 publications
(115 citation statements)
references
References 33 publications
3
101
2
7
Order By: Relevance
“…Our findings refute those of O'Connor et al 8 and our meta-analysis, 11 both of which demonstrated the FMS to have lower sn and higher sp. The current data indicate that the FMS was more sensitive than specific.…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations
“…Our findings refute those of O'Connor et al 8 and our meta-analysis, 11 both of which demonstrated the FMS to have lower sn and higher sp. The current data indicate that the FMS was more sensitive than specific.…”
Section: Discussioncontrasting
confidence: 57%
“…11 O'Connor et al established the AUC for the injury classifications of any injury (0.58), overuse injury (0.52), and serious injury (0.53) of the FMS to be slightly better than chance in predicting injury in each of the 3 categories. Our meta-analysis results 11 established the comprehensive AUC of the included FMS literature at 0.587. Based on the results of these 3 studies, we can establish that the FMS was slightly better than chance in predicting injury.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the abovementioned methodological issues pertaining to injury prediction, nonetheless there has been a range of research investigating the relationships between the incidence of injury with player wellness, 20 musculoskeletal screening test scores, 21 fitness levels, 22 and training load. 23 As many elite team sport athletes are being assessed in some capacity on an almost daily basis, the ability to analyze these athletes at the individual level has never been more feasible.…”
Section: Validating the Decision Not To Trainmentioning
confidence: 99%